"These Things Took Place as Examples for Us": On the Theological and Ecumenical Significance of the Lutheran Sola Scriptura. Issue 3 (September 2016) - Alfsvåg, Knut
Abstract: The principle of sola Scriptura does not suggest a reading of the Bible in a room void of context, but points to the fact that the unity of church, canon, and confession defines the identity of the Christian church. The Lutheran Reformation was an attempt to retrieve this perspective at a time when it had become obscure. This retrieval corresponds to certain tendencies on the contemporary scene; it remains to be seen, however, how far convincing answers in this way can be provided for today's burning issues.